Miscelánea ibérica (2) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
This article deals with several Iberian words. Teistea might not be a verb but a derivative with the suffix -ste. No objection to that barton would mean ‘wife’ or similar. There exists difference between erder and erdi, the first is effectively related with Basque erdi, ‘half, middle’; the second is another word.
Keywords: teistea; barton; erder; erdi; Iberian